Mental Distress and Human Rights Violations During COVID-19: A Rapid Review of the Evidence Informing Rights, Mental Health Needs, and Public Policy - Rahman, Muhammad; Ahmed, Rabab; Moitra, Modhurima; Damschroder, Laura; Brownson, Ross; Chorpita, Bruce; Idele, Priscilla; Gohar, Fatima; Yen Huang, Keng; Saxena, Shekhar; Lai, Joanna; Swartling Peterson, Stefan; et al. (Frontiers in Psychiatry, 2021)
Background: COVID-19 prevention and mitigation efforts were abrupt and challenging for most countries with the protracted lockdown straining socioeconomic activities. Marginalized groups and individuals are particularly vulnerable to adverse effects of the pandemic such as human rights abuses and violations which can lead to psychological distress. In this review, we focus on mental distress and disturbances that have emanated due to human rights restrictions and violations amidst the pandemic.We underscore how mental health is both directly impacted by the force of pandemic and by prevention and mitigation structures put in place to combat the disease.
Open Access
Keywords: Mental and behavioral health; Human rights; Lockdown; Health care worker [non-MESH]; Stigma and discrimination; Vulnerable populations; LMICs (low and middle income countries)